STUDY OF INFLUENCE ANTISEPTIC SUPPOSITORIES ON ADHESIVE PROPERTIES OF MICROORGANISMS - Коваленко І. М. (World of Medicine and Biology, 2014)
The results of studying the effect of antimicrobial agents on the adhesion of clinical strains of gram-positive and gram-negative microorganisms. Studies have shown that antiseptics altered adhesion of bacteria. The lowest index of adhesiveness observed in the presence of deseptol - 13,1% in museum strains of staphylococcus and 21.9% for clinical, that in 7,6 and 4,5 times less compared with the control.